2005
DOI: 10.1038/sj.ejhg.5201469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the APOC3 Sst I SNP on fasting triglyceride levels in men heterozygous for the LPL P207L deficiency

Abstract: Lipoprotein lipase (LPL) plays a major role in triglyceride (TG)-rich lipoprotein catabolism. A mutation at codon 207 (P207L) in the exon 5 of the LPL gene has been associated with 50% reduction in postheparin plasma LPL activity and significant increase in plasma TG levels in heterozygous individuals with low HDL. However, heterogeneity in fasting TG concentrations among these carriers suggests that other factors may be involved in the expression of this hypertriglyceridemic state. Indeed, previous studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…A recent study has observed that the apo CIII-SstI SNP increases fasting TG levels among carriers of the LPL P207L mutation. 30 Reilly et al 31 have also recently…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has observed that the apo CIII-SstI SNP increases fasting TG levels among carriers of the LPL P207L mutation. 30 Reilly et al 31 have also recently…”
Section: Discussionmentioning
confidence: 99%
“…Examples of functional influence of single or multiple polymorphisms on the effect of a nearby mutated gene are rare, but nevertheless reported (15)(16)(17)(18)(19). For example, in hereditary thrombotic thrombocytopenic purpura due to mutation in the ADAMTS13 gene, the polymorphisms R7W and Q448E -that were shown to have positive modifying effect on the gene function in the absence of the mutation -enhanced the detrimental effect of the missense mutation (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to these variants, the E255G proband was homozygous for the previously reported LPL W86G 15 and the H321L carrier was heterozygous for LPL P207L 18 suggesting that these variants in APOA5 are making a rather minor contribution to the disorder. We expressed these APOA5 variants together with those previously reported 1,2,5 and carried out functional studies in vitro obtaining novel insights into the structure: function relationship of apoAV.…”
Section: Discussionmentioning
confidence: 89%
“…LPL P207L has been well characterized in vitro 24 and in vivo. 18 In a study of 34 P207L carriers, in the presence of a APOC3 TG-raising SNP, mean TG were 10.31 mmol/L compared to 5.58 mmol/L in noncarriers of this SNP. 18 We propose that the presence of APOA5 H321L and S19W compound the effect of P207L, resulting in pretreatment TG levels reaching 63 mmol/L, considerably higher than that reported by Garenc et al 18 …”
Section: Apoav-l321mentioning
confidence: 99%
See 1 more Smart Citation